2018
DOI: 10.1080/08998280.2018.1463041
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic response to cyclin D–dependent kinase 4/6 inhibitor in refractory poorly differentiated neuroendocrine carcinoma of the breast

Abstract: Neuroendocrine tumors are a rare subset of breast carcinomas. Commonly, platinum-based doublet is used as a systemic treatment option for high-grade neuroendocrine carcinomas from lung, gastrointestinal, and genitourinary origins. In comparison to other breast cancers, neuroendocrine carcinomas have unique genomic features and different treatment strategies. We present a patient with high-grade neuroendocrine carcinoma of the breast who had a successful and durable response to the cyclin D-dependent kinase (CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…4,8,9,46,47 The molecular alterations (PIK3CA, TP53, RB1, CCND1) in breast NEC are common in invasive ER þ (luminal) ductal carcinomas of no-special-type suggesting potential relevance of cell cycle (CDK4/6 inhibitors) in isolated cases of this rare cancer. 48,49 There are also ongoing clinical trials with cell cycle inhibitors aimed to treat patients with lung and head/neck cancers harboring CCND1 amplification (trials: NCT03356223 and NCT02785939). Although FGFR inhibitors have been recently considered as a promising therapeutic option in breast cancer, the preliminary clinical data with FGFR inhibitors have yielded disappointing results.…”
Section: Ngs and Archer Fusion Resultsmentioning
confidence: 99%
“…4,8,9,46,47 The molecular alterations (PIK3CA, TP53, RB1, CCND1) in breast NEC are common in invasive ER þ (luminal) ductal carcinomas of no-special-type suggesting potential relevance of cell cycle (CDK4/6 inhibitors) in isolated cases of this rare cancer. 48,49 There are also ongoing clinical trials with cell cycle inhibitors aimed to treat patients with lung and head/neck cancers harboring CCND1 amplification (trials: NCT03356223 and NCT02785939). Although FGFR inhibitors have been recently considered as a promising therapeutic option in breast cancer, the preliminary clinical data with FGFR inhibitors have yielded disappointing results.…”
Section: Ngs and Archer Fusion Resultsmentioning
confidence: 99%
“…A recent study suggested that menin has an essential role as a FOXA1 and GATA3-bound enhancer, leading to aggressive features of ERpositive breast cancers and probably also to aromatase inhibitor resistance via activating ESR1 mutations [42]. Furthermore, ESR1 was found to be mutated in a case study of an NEBC patient whose cancer did not respond to the commonly used platinum-based chemotherapy or hormone-based treatment [43]. The mutation was found when genotyping a patient's liver lesion that had been treated with the cyclin D-dependent kinase 4/6 inhibitor palbociclib.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of a cyclin-dependent kinase (CDK) 4/6 inhibitor to an aromatase inhibitor has significantly changed the prognosis of metastatic patients, both naïve and pre-exposed to ET, providing a great benefit in terms of PFS and, at least in some studies, in terms of OS [ 52 54 ]. Namely, the combination of palbociclib and fulvestrant has been used in the treatment of a patient affected from NEBC, with positive results [ 55 ]. The patient, affected by high-grade NEBC, was refractory to platinum-based chemotherapy as well as first-line hormonal treatment with tamoxifen and leuprolide, but showed a durable response to fulvestrant plus palbociclib.…”
Section: Methodsmentioning
confidence: 99%